Ratio of height to thyromental distance as a predictor of difficult laryngoscopy: A prospective observational study - Suvarna Kaniyil; Krishnadas Anandan; Sanjith Thomas (Wolters Kluwer Medknow Publications, 2018)
Background and Aim: Various airway indices are used either singly or in combination to predict difficult laryngoscopy. Recently introduced ratio of height to thyromental distance (RHTMD) is reported to have better predictability. We aimed to assess the prediction of difficult laryngoscopy by RHTMD and compared it with other indices. Material and Methods: In this prospective, single-blinded comparative observational study, 300 adult patients of either gender scheduled to receive general anesthesia were assessed. Airway indices, like RHTMD, thyromental distance, modified Mallampati test, and upper lip bite test, were assessed and correlated with Cormack and Lehane's laryngoscopic grading. The validity parameters like specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated for each test. Effect of combining all the indices was also analyzed. Receiver operating characteristic curves were constructed and optimal cutoff value for the quantitative indices was calculated. Results: The incidence of difficult laryngoscopy in our study was 5.33%. Of the four indices, the single best test was RHTMD, with better sensitivity, high specificity, NPV, and accuracy and with good PPV. A combination of all the indices resulted in 100% sensitivity and higher specificity. Conclusions: RHTMD is a single best preoperative test for predicting difficult laryngoscopy. A combination of tests has higher sensitivity and specificity with better discriminative power. Therefore indices should be used in combination in the preoperative airway assessment of adult patients.